LECTURES IN MEDICAL EDUCATON: WHAT STUDENTS THINK? - Mustafa, Tajammal; Farooq, Zerwa; Asad, Zunaira; Amjad, Rabbia; Badar, Iffat; Chaudhry, Abdul Majeed; Khan, Mohammad Amer Zaman; Rafique, Farida (Journal of Ayub Medical College Abbottabad, 2014)
Background: The volume of medical knowledge has increased exponentially and so has the need to improve the efficiency of current teaching practices.With increasing emphasis on interactive and problem based learning, the place of lectures in modern medical education has become a questionable issue. Objectives were to assess the perspective of undergraduate medical students regarding the role and effectiveness of lectures as a mode of instruction as well as the ways and means that can be employed to enhance the effectiveness of lectures. Methods: A cross sectional study was carried out among 2nd to final year medical students from five medical colleges including both private and public sector institutions. A total of 347 students participated by completing a structured questionnaire. Data was analyzed using SPSS-17. Results: Sixty seven percent students considered lectures as a useful mode of instruction (47% males and 77% females), whereas 83% of the students reported that clinical sessions were superior to lectures because of small number of students in clinical sessions, active student participation, enhanced clinical orientation, and interaction with patients. About 64% responded that lectures should be replaced by clinical sessions. Majority of the students (92%) reported not being able to concentrate during a lecture beyond 30 minutes, whereas 70% skipped lectures as they were boring. A significantly greater proportion of male respondents, students from clinical years, and those who skipped lectures, considered lectures to be boring, a poor utilization of time and resources, and could not concentrate for the full duration of a lecture compared to females, students from preclinical years, and those who do not skip lectures, respectively. Conclusion: Lecturing techniques need to be improvised. The traditional passive mode of instruction has to be replaced with active learning and inquiry based approach to adequately utilize the time and resources spent on lectures. Keywords: Lectures, medical students, medical education, clinical sessions, active learning